Agent Hamilton [videorecording (DVD)] - Persbrandt, Mikael, 1963-; Mubarak, Saba; August, Pernilla, 1958-; Guillou, Jan, 1944- (MHZ Networks Home Entertainment, 2017)
In the Interest of the Nation - Masked soldiers attack a vehicle loaded with high-tech missiles in an attempted smuggling operation in Uzbekistan. Meanwhile, a Swedish engineer is kidnapped in Ethiopia. But Not if It Concerns Your Daughter - Carl Hamilton's family was wiped out in a revenge attack years ago. Now, those painful memories resurface as Hamilton's seven-year-old goddaughter is abducted by a renegade Saudi prince in a plot targeting the girl's mother.